An Investigation of the Efficiency of Introductory Economics Courses - R.W. Crowley; D.A. Wilton (Queen's University, Department of Economics, 1972)
In most academic circles, inquiring into the value and/or success of education has been considered akin to questioning motherhood. Economic research on the "value"of education has centred largely on two issues; the first one being human capital theory and the structure of earnings, and the second being the contribution of education to economic growth. This paper represents the first report of a project designed to examine the "efficiency" of the first year economics course. The first part of the project is to identify and quantify the factors that account for student performance in the introductory course. Secondly, the amount of "new" economic knowledge retained over subsequent years will be examined. Finally, with learning and retention factors carefully analysed, an attempt will be made to explore techniques for increasing "efficiency" in the introductory economics course. The ultimate question towards which ths research is directed is whether there are significant effects from varying the teaching-learning configuration or not.
Keywords: 330